2001
DOI: 10.7863/jum.2001.20.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic vein and hemodialysis fistula: surgeon's observation versus color Doppler ultrasonographic findings.

Abstract: The aim of this study was to evaluate whether preoperative color Doppler ultrasonography improves immediate success rates of arteriovenous fistulas for dialysis. One hundred twenty-four patients with chronic renal failure underwent color Doppler ultrasonographic examination of both arms, including the cephalic vein, before arteriovenous fistula construction. Patients were randomly divided into 2 groups: A and B. In group A, there were 52 patients, and the surgeon planned to construct arteriovenous fistulas dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 7 publications
6
86
0
4
Order By: Relevance
“…Our finding that immediate failure is significantly reduced by preoperative ultrasound is consistent with another randomized trial, which showed significantly less failure (6% versus 25%) on the day of surgery in the ultrasound compared with the clinical group (19). Inadequate vessels can be identified by ultrasound, which reduces the rate of immediate failure (11,12,24).…”
Section: Discussionsupporting
confidence: 79%
“…Our finding that immediate failure is significantly reduced by preoperative ultrasound is consistent with another randomized trial, which showed significantly less failure (6% versus 25%) on the day of surgery in the ultrasound compared with the clinical group (19). Inadequate vessels can be identified by ultrasound, which reduces the rate of immediate failure (11,12,24).…”
Section: Discussionsupporting
confidence: 79%
“…Perhaps vascular (ultrasound) mapping provided more objective assessment of the cephalic vein until the axillary vein. In our study, the ultrasound mapping not just the size of the vessels but also its depth and presence of stenosis similar to a report elsewhere (12).…”
Section: Discussionsupporting
confidence: 90%
“…The inability to maintain the benefit of using preoperative ultrasound mapping could be due to failure caused by various factors such as thrombosis or stenosis of the venous limb due to multiple puncture or stenosis at the juxtaarterial anastomosis. Similar finding was reported by I. Mihmanli et al, where they concluded that preoperative duplex US scanning improved short-term AVF patency, from 75% to 94%, compared with physical examination alone (8).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In selected patients, additional imaging is indicated to exclude the presence of central vein stenosis or thrombosis. A dramatic increase in fistula placement was observed by several centers after implementation of routine preoperative vascular mapping (2,7,9,(25)(26)(27)(28). Among patients who are referred for their initial vascular access surgery, placement of a forearm fistula is feasible in only 40 to 50% (2,3,7,9).…”
Section: Why Should We Increase Fistula Use?mentioning
confidence: 99%